PENERAPAN BIMBINGAN KONSELING DI SMPN 1 TELUKJAMBE TIMUR - Ahmad, Sami Nuari; Halizah, Siti Nur; Rahmawati, Suci; Jannah, Wardatul; Farida, Nur Aini (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Guidance and counseling are activities that are closely related to everyday human life, where every individual, including students, faces various problems. In the school environment, the role of guidance and counseling teachers is very important in helping students overcome academic and personal problems. SMPN 1 Telukjambe Timur is the focus of this study to analyze the implementation of guidance and counseling and the challenges faced in its implementation. This study aims to describe the implementation of guidance and counseling at SMPN 1 Telukjambe Timur, identify supporting and inhibiting factors, and analyze problems that often arise in the implementation of guidance and counseling services at the school. The method used is descriptive qualitative with data collection techniques through observation, documentation, and interviews. The research informants consisted of guidance and counseling teachers and a student who had consulted. The results of the study showed that one of the main problems in the implementation of guidance and counseling is the perception of students who consider guidance and counseling teachers as peers. This affects the effectiveness of the services provided, thus impacting the quality of guidance received by students. Guidance and counseling at SMPN 1 Telukjambe Timur requires more attention to understanding the role of guidance and counseling teachers so that the relationship that is established remains professional and effective in solving student problems.